Comparison of Sexual Dysfunction in Women with Migraine and Multiple Sclerosis (MS) - Askari, Fariba (Maedica (Bucur), 2016)
Migraine and multiple sclerosis (MS) are two neurologic disorders that influence different aspects of women who are affected. Sexual function is one of the co-morbidities that are not considered well in such cases. The goal of this study to evaluate sexual function in women experiencing either migraine or MS. Eighty six married migraineus patients and 86 age- matched married MS cases were asked to fill out valid and reliable Beck depression inventory (BDI) and FSFI (Female Sexual Function Index ) questionnaires. BDI score was higher in women with migraine than MS cases and BDI scores in both groups were high in cases with sexual dysfunction. BDI score was significantly correlated with total FSFI and its subscales in both groups. Multiple linear regression analysis between the FSFI as a dependent variable and age, BDI and education level as independent variables showed that age and BDI are independent predictors of FSFI in both groups. Sexual dysfunction should be considered in women with either MS or migraine.